Kepuasan Konsumen Memoderasi Pengaruh E-Service Quality dan Promosi Terhadap Keputusan Pembelian pada Aplikasi Zenius di Indonesia - Lukiyana, Lukiyana; Ramafita, Dewi (Ekonomis: Journal of Economics and Business, 2024)
This study aims and has the intention to test and examine how much influence E-Service quality and promotion have on purchasing decisions as well as a moderating variable, namely consumer satisfaction. The research population used a sample of 304 respondents who are users of the Zenius application in Indonesia. The technique used for data collection in this study used a sampling method, namely non-probability sampling, purposive sampling, to be precise, by distributing research questionnaires. The data processing system is carried out using smartPLS with a view to testing hypotheses. The current results in this study prove that E-service quality has evidence of a significant positive influence on purchasing decisions, promotion has evidence of a significant positive influence on purchasing decisions, consumer satisfaction has a significant positive influence on purchasing decisions, consumer satisfaction is also proven significant and can moderate the effect of E-service quality on purchasing decisions, consumer satisfaction has significant evidence and can moderate the effect of promotions on purchasing decisions. Therefore, this study recommends that Zenius carry out promotions not only on social media but also through television by displaying several talents that are of interest so that consumers can make purchasing decisions to subscribe to various study packages in the Zenius application, because several respondents in This study states that some new users are not aware of the learning packages offered by Zenius. Zenius is also expected to maintain its quality of service in serving consumers or users of the Zenius application so that consumers are more comfortable when they have problems, when making transactions or when using the features in the Zenius application.